IMPLEMENTATION OF DIJKSTRA'S ALGORITHM IN DETERMINING THE SHORTEST PATH (CASE STUDY: SPECIALIST DOCTOR SEARCH IN BANDAR LAMPUNG) - Rakhmat Dedi Gunawan; Riduwan Napianto; Rohmat Indra Borman; Irma Hanifah (STMIK Pringsewu Lampung, 2019)
The shortest route from a trip will shorten the travel time. Likewise, in the case of the search for specialists. In the search for a specialist the community must come to the health service to ask for specialist information needed. The shortest path is a problem to find the path between two or more vertices in the minimum numbered weighted graph. To make it easier to solve the shortest path problems, a search algorithm is needed. The algorithm that is commonly used in solving problems in finding the shortest path or path is Dijkstra's algorithm. The basic idea of Dijkstra's own algorithm is to find the cost value closest to the destination that functions in a weighted graph. In this study, the Dijkstra algorithm finds the shortest path based on the smallest weight from one point to another, so that it can help provide path choices. Based on the trial of Dijkstra's algorithm, it has the ability to find the shortest path, because in the algorithm each graph is selected the side with the minimum weight that connects a selected node with another node that has not been selected.